Effect of BCG vaccination against Mycobacterium tuberculosis infection in children: systematic review and meta-analysis. (5th August 2014) - Roy, A; Eisenhut, M; Harris, R J; Rodrigues, L C; Sridhar, S; Habermann, S; Snell, L; Mangtani, P; Adetifa, I; Lalvani, A; Abubakar, I
Abstract : Objectives To determine whether BCG vaccination protects against Mycobacterium tuberculosis infection as assessed by interferon γ release assays (IGRA) in children. Design Systematic review and meta-analysis. Searches of electronic databases 1950 to November 2013, checking of reference lists, hand searching of journals, and contact with experts. Setting Community congregate settings and households. Inclusion criteria Vaccinated and unvaccinated children aged under 16 with known recent exposure to patients with pulmonary tuberculosis. Children were screened for infection with M tuberculosis with interferon γ release assays. Data extraction Study results relating to diagnostic accuracy were extracted and risk estimates were combined with random effects meta-analysis. Results The primary analysis included 14 studies and 3855 participants. The estimated overall risk ratio was 0.81 (95% confidence interval 0.71 to 0.92), indicating a protective efficacy of 19% against infection among vaccinated children after exposure compared with unvaccinated children. The observed protection was similar when estimated with the two types of interferon γ release assays (ELISpot or QuantiFERON). Restriction of the analysis to the six studies (n=1745) with information on progression to active tuberculosis at the time of screening showed protection against infection of 27% (risk ratio 0.73, 0.61 to 0.87) compared with 71% (0.29, 0.15 to 0.58) against active tuberculosis. Among those infected, protection against progression to disease was 58% (0.42, 0.23 to 0.77). Conclusions BCG protects against M tuberculosis infection as well as progression from infection to disease. Trial registration PROSPERO registration No CRD42011001698 (www.crd.york.ac.uk/prospero/ ).